Labour market and wage developments in Europe 2015 (Brussels, 2015)
"Labour market developments have been improving against the background of a gradual economic recovery in the EU. Unemployment in the EU has continued to fall and job finding rates have modestly improved. However, despite its recent fall, unemployment remains high.